A Historiography Paper on Japan’s Colonization of Manchuria and Taiwan - Huang, Gelin (Technium Social Sciences Journal, 2021)
1905 witnessed Japan’s victory over Russia. The whole of Asia was inspired by this war, even including the Chinese who until now have viewed Japan as their chief enemy in the past more than one hundred years. Many non-white people regarded this victory as the first victory that a colored race gained against white people. This war also marked the moment that Japan turned into one of the great powers in the world. However, disappointingly some Asian states, like China and Korea, soon discovered that what they can get from the victory of Japan was only the fate of being invaded or colonized. With regard to China, two territories of this country had been colonized by Japan for a relatively long period of time, namely Taiwan from 1895 to 1945 and Manchuria from 1931 to 1945. Admittedly, according to the different situations (geographically, ethnically, economically and so on) in these two places, Japan employed two distinct strategies to rule these two areas. Especially in Manchuria, the Japanese built a puppet state—Manchukuo—to control the local people, and in Taiwan, the Government-General of Formosa was the center of Japan’s bureaucracy on this island. Yet, it is not wrong to say that the Empire of Japan wanted to transform both these two areas into her permanent territory. Thus, it is proper for us to talk about Japan’s rule in these two regions together. This article will focus on three books on this subject. Two of the three books are about Taiwan, namely, Chin-Ming Ka’ Japanese Colonialism in Taiwan: Land Tenure, Development, and Dependency, 1895-1845 and Leo T.S. Ching’s Becoming “Japanese”: Colonial Taiwan and the Politics of Identity Formation. The one mainly concerning Manchuria is Miriam Kingsberg’s Moral Nation: Modern Japan and Narcotics in Global History. This paper provides a review of these books.